Decorrências do processo formativo com vistas à educação inclusiva no fazer pedagógico de egressos dos cursos de Licenciatura da UFSM - Oliveira, Clarissa da Silva (2013)
The present work was developed in the line of research of Special Education of the Master course in Education at Federal University of Santa Maria (UFSM). The study consists of an investigation about the relevance of the course in Fundamentals of Special Education, inserted in the curriculum of undergraduate courses at UFSM, given the Ministerial Decree N º. 1.793/94. From experiences as substitute teacher in the course of Foundations of Special Education in the Department of Special Education at UFSM, this study has as the main focus to investigate the relevance of this discipline considering the pedagogical practice of the teachers graduated at UFSM. Taking the assumptions of Schön (1992) I saw as a premise the need of reflecting about the practice developed by myself as a teacher. The study is also based on the Historical-Cultural theory of Vygotsky (1991), in which the author believes that the man is a social being formed within an cultural environment historically defined, considering that the development is the result of social interactions. The research was characterized as qualitative descriptive, and featured with a semi-structured interview as a tool for data collection. The interview was conducted with six graduated teachers of the following courses: Visual Arts - Degree in Design and Plastic, teaching in Mathematics - night course and teaching in Music at UFSM. The interpretation and analysis of results were based on the technique of result analysis of Bardin (2008). The conclusions reaffirm that one of the elements for graduate a teacher with a pedagogical view taking into account the scholar inclusion is based on the warranty of an initial degree enabling that the future regular teacher changes its values and concepts, developing appropriate pedagogical actions in the process of scholar inclusion. Furthermore, the interview registered as a suggestion/claim an expansion of the workload of the course, enabling better preparation for the challenge that the educational context is proposed.